2006
DOI: 10.1249/01.mss.0000227537.13175.1b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Education and Activity Levels on Academic Achievement in Children

Abstract: Although academic achievement was not significantly related to physical education enrollment, higher grades were associated with vigorous physical activity, particularly activity meeting recommended Healthy People 2010 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
373
4
26

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(420 citation statements)
references
References 18 publications
17
373
4
26
Order By: Relevance
“…In this study, it was suggested that the effect of tag on reaction time is high. Recently, it was reported that whole body motions requiring quick movement such as a quick turn, and thinking strategies such as situational judgment, are effective for promoting development of a cerebral motion control function or an intelligence function (6,10). From now preschool teachers should introduce these exercises positively into an exercise program.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was suggested that the effect of tag on reaction time is high. Recently, it was reported that whole body motions requiring quick movement such as a quick turn, and thinking strategies such as situational judgment, are effective for promoting development of a cerebral motion control function or an intelligence function (6,10). From now preschool teachers should introduce these exercises positively into an exercise program.…”
Section: Discussionmentioning
confidence: 99%
“…In general the activities and programs that improve children's executive functions (Hillman and Kramer, 2008) improving the 8-12 year-olds' cognitive flexibility and creativity, and significantly more so than did standard physical education (Diamond and LEE, 2011;TUCKMAN, 1986). Another authors postulate that bimanual coordination (CASTELLI and Hillman, 2007), resistance training (Coe, 2006), several sports practice that requiring sustained attention, work memory, and disciplined action may improve the executive function (Diamond and Lee, 2011) in this context the Karatê practice deserve more investigations about their effects upon this functions. RAFAEL FERREIRA LIMA, VERNON FURTADO DA SILVA, GLAUBER LAMEIRA DE OLIVEIRA, TALITA ADÃO PERINI DE OLIVEIRA, JOSÉ FERNANDES FILHO, JOÃO GUILHERME RODRIGUES MENDONÇA, CÉLIO JOSÉ BORGES, ANGELIETE GARCES MILITÃO, IVETE DE AQUINO FREIRE, JOÃO RAFAEL VALENTIM-…”
Section: Introductionmentioning
confidence: 99%
“…If this is the case, and with reference to the 'neural interference' and more cognitive demands for movement reported by Lambourne and Tomporowski [9] it would be advantageous in future research to ascertain the fitness of the children prior to the session. The reporting of positive relations between fitness and standardised achievement test performance [4] and increased performance in core academic classes in children who were able to engage in more vigorous physical activity [5] may imply that fitter children can cope with more neural interference before it affects cognitive function after exercise. In summary, the present study provides no strong evidence that exercise intensity moderates the improvement in pre-adolescent post-exercise academic ability.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that children gain cognitive benefits from physical activity [1,2] with greatest improvements seen in complex mental processing [3]. Standardised achievement in maths and reading [4] as well as increased performance in core academic classes has been reported for children who participate in vigorous physical activity outside of school [5].…”
Section: Introductionmentioning
confidence: 99%